A new species of Podocinum Berlese (Acari: Podocinidae) and a key to species of the genus from China - Yan, Yi; Jin, Dao-Chao; Guo, Xian-Guo; Guo, Jian-Jun (Zootaxa, 2011)
Mites were collected from leaf litter and the fur of a wild rodent (Niviventer fulvescens ) in Guizhou Province of China, and described as Podocinum guizhouense sp. nov. (Podocinidae). This is the first report of Podocinidae from a wild rodent host, but this ecological association may be accidental. A key to the females of Podocinum from China is provided.